Breakthrough percepts of famous faces. (4th October 2018) - Alsufyani, Abdulmajeed; Hajilou, Omid; Zoumpoulaki, Alexia; Filetti, Marco; Alsufyani, Hamed; Solomon, Christopher J.; Gibson, Stuart J.; Alroobaea, Roobaea; Bowman, Howard
Abstract: Recently, we showed that presenting salient names (i.e., a participant's first name) on the fringe of awareness (in rapid serial visual presentation, RSVP) breaks through into awareness, resulting in the generation of a P3, which (if concealed information is presented) could be used to differentiate between deceivers and nondeceivers. The aim of the present study was to explore whether face stimuli can be used in an ERP‐based RSVP paradigm to infer recognition of broadly familiar faces. To do this, we explored whether famous faces differentially break into awareness when presented in RSVP and, importantly, whether ERPs can be used to detect these breakthrough events on an individual basis. Our findings provide evidence that famous faces are differentially perceived and processed by participants' brains as compared to novel (or unfamiliar) faces. EEG data revealed large differences in brain responses between these conditions.